Dramatising the Conflicts of Nation and the Body: Displacement in Charlotte and Emily Brontë's Poetry of ‘Home’ and ‘Exile’ Dualities - Alexandra Guimaraes, Paula (Miscelánea: A Journal of English and American Studies, 2008)
For Gregory Orr, the best way to respond to the chaotic unpredictability of our being is through the personal lyric because it “dramatizes inner and outer experience” by “clinging to embodied being”. The self in the personal lyric of the Brontés (Charlotte and Emily) is either ‘home’ or ‘away’, facing internal or external division or fracture, and in search of a prospective identity (personal and national) or a chosen location. The conflicts of nation (whether they are presented in a real or fictionalised manner) are simultaneously reflected in the conflicts of the body itself; and the word ‘home’ —a metaphor for both ‘place’ and ‘being’— assumes different but related nuances (from the familiar hearth and the exalted homeland to the poet’s mind, Nature or God’s bosom). There is an evasive attempt to overcome social and political coercions that create both confinement and displacement, but whether the Brontés choose to stay at home or are compelled to leave, they remain ‘exiles’. Ultimately, for these poets, it will be exilic displacement which will act as a ‘spur to creativity’ and define authorship.
Keywords: Body; Home; Nation; Displacement; Exile